What Does Silicon Valley Have to Do with Jerusalem? - Peterson, Gregory R. (Zygon, 2004)
Abstract. Adapted from the introductory chapter of Minding God: Theology and the Cognitive Sciences (Peterson 2003), I here lay out a general approach for a dialogue between theology and cognitive science. Key to this task is an understanding of theology as the science or study of meaning and purpose. I give reasons why theology should be thought of in this sense and the potential fruitfulness of this approach.